Generation and characterization of mice bearing null alleles of nradd/Nrh2. Issue 12 (12th November 2016) - Unsain, Nicolas; Dorval, Genevieve; Sheen, Jae Hyung; Barker, Philip A
Abstract: The Neurotrophin receptor associated death domain gene ( Nradd/Nrh2/Plaidd ) is a type I transmembrane protein with a unique and short N‐terminal extracellular domain and a transmembrane and intracellular domain that bears high similarity to the p75 neurotrophin receptor ( p75NTR/Ngfr ). Initial studies suggested that NRADD regulates neurotrophin signaling but very little is known about its physiological roles. We have generated and characterized NRADD conditional and germ‐line null mouse lines. These mice are viable and fertile and dońt show evident abnormalities. However, NRADD deletion results in an increase in the proportion of dorsal root ganglion neurons expressing p75NTR. The NRADD conditional and complete knockout mouse lines generated are new and useful tools to study the physiological roles of NRADD. Birth Defects Research (Part A) 106:605–612, 2016. © 2016 Wiley Periodicals, Inc.